Microhabitat use of juvenile reef fish and its implications in the use of remote sensing techniques in delineating optimal reefs fish habitats - Ticzon, Victor S. (Marine Science Institute, College of Science, University of the Philippines Diliman, 2014)
Strong habitat and adult reef fish associations have been well established in literature. However, relatively little is known about the habitat associations of juvenile reef fish. In this study, we quantified microhabitat association with juvenile reef fish community structure between reefs that has experienced minimal human intervention (i.e.,Ngederrak Reef), and one that has been exposed to high fishing pressure (Bolinao-Anda Reef Complex or BARC). The goal is to look at the role of microhabitat structure in influencing juvenile reef fish diversity and abundance in these two sites, and how microhabitat types can effectively act as surrogate measures of diversity and abundance of juvenile reef fish for possible broad scale assessment applications. the result demonstrated the strong interaction of juvenile reef fish with specific coral reef microhabitats in Ngederrak reef. However, microhabitat and juvenile reef fish association was weakly manifested in the exploited reefs of BARC. Overall, the results have important implications not only in management, but also in modeling the impacts of habitat loss on reef fish community.